The Influence of Physical Activity, Nutritional Status, Age, and Gender on the Health-Related Quality of Life Among Adolescents in Bolaang Mongondow Regenc - Kumala Dewi, Citra; Fatimawali, Fatimawali; Posangi, Jimmy (Al Makki Publisher, 2024)
This study analyzed the influence of Physical Activity, Nutritional Status, Age, and Gender on Adolescent Health and Quality of Life in Bolaang Mongondow Regency. This was an analytic study with a cross-sectional approach conducted in junior and senior high schools in Bolaang Mongondow Regency in October 2023 with a total sample of 406. The results of the study found that physical activity and nutritional status had a p>0.05 value in all domains, while the age variable had a p<0.05 value in the psychological and social domains, the gender variable had a p<0.05 value in the psychological domain, then to analyze the most influential variables, the researcher conducted a logistic regression test and obtained the results of the gender and age variables having the most decisive influence on the quality of life of adolescent health in the psychological domain by 8.6%. This study concludes that Physical Activity and Nutritional Status are unrelated and do not affect the quality of life of adolescents in the Bolaang Mongondow district. At the same time, the variables of age and gender influence only the psychological and social domains of quality of life health; gender and age variables have the most decisive influence. This study implies that Physical Activity and Nutritional Status are not the main factors that influence the quality of life of adolescents in Bolaang Mongondow Regency. However, Age and Gender have a more significant influence, especially on psychological aspects.